2022
DOI: 10.1177/01968599221089236
|View full text |Cite
|
Sign up to set email alerts
|

Virtual vs. Real Self: Gendered Presentation and Everyday Performance of Virtual Selfhood – A Case Study of Pakistan

Abstract: The presentation and performance of women's selfhood and identity in Pakistan, in both the real and the virtual world, is dictated and shaped by the male-dominated cultural mores of Pakistan. Therefore, drawing upon Goffman's notion of self-presentation and everyday performance of selfhood, this paper explores digitally active Pakistani women's selfhood and identity presentation through qualitative interviews with ten Pakistani women from diverse backgrounds. Participants’ narratives revealed identity conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…As [29] argued, ease of use and subjective norm anticipate technology adoption. For example, a group of individuals with smartphones will likely affect the other people intending to buy the smartphones for their usage [84].…”
Section: Ipma Discussion On Resultsmentioning
confidence: 99%
“…As [29] argued, ease of use and subjective norm anticipate technology adoption. For example, a group of individuals with smartphones will likely affect the other people intending to buy the smartphones for their usage [84].…”
Section: Ipma Discussion On Resultsmentioning
confidence: 99%
“…As shown, all the hypotheses are accepted and the proposed effects of independent variables on the endogenous variables are supported. This research examined the factors affecting Metaverse Experience Browser Acceptance among higher education students (Aksar et al, 2022) in the United Arab Emirates. The primary constructs are adopted from different studies conducted in different settings and scenarios.…”
Section: Outer Model Analysismentioning
confidence: 99%
“…A quantitative study related the uses of social media to women's psychological well-being and described a positive association (Ali Aksar et al ., 2020). However, a qualitative study concluded that offline culture is replicated in virtual communities and women adopt strategies to hide their online identity to secure themselves from cultural forces (Aksar et al ., 2022).…”
Section: Integration Of Social Media Psychological Well-being and Womenmentioning
confidence: 99%